Analisis Pengaruh Perubahan Nilai Total Moisture Dan Ash Content Terhadap Nilai Kalori Batubara Di Unit Pelabuhan Pt Bukit Asam Tbk Tarahan Bandar Lampung - Alldino Hernanto; Janiar Pitulima; Delita Ega Andini (MINERAL, 2020)
The coal industry emphasizes the quality of coal because quality will always be directly related to consumers and the company's revenue because the higher the quality of coal, the more expensive the selling price of coal, therefore this research was conducted to determine the difference in coal quality in railroad cars (demolition) and when analyzing for stockpile, the effect of total moisture and ash content on coal calories and the factors causing these changes. In this study, qualitative and quantitative methods were used where the steps taken in this research were sampling in the railroad car and in the stockpile and then using the proximate analysis and analysis of coal calories from the analysis and correlation and regression analysis to determine the effect of total moisture and ash content. against coal calories. The proximate analysis of the coal samples is disassembly total moisture which is 8.49% ar, in the stockpile, which is 10.32 % ar ash content demolition which is 5.37, in the stockpile which is 8.62 % ar and the calorific value of demolition is 7181 cal/gr, in the stockpile that is 6800 kal / gr so that each of the total moisture parameters, ash content and calorific value changes by 1.40 % ar, at 3.25 % ar, and by 400 Kal / gr. Based on the regression results, the total effect of total moisture and ash content on the first calorie each increase of 1 % ar the total moisture value will reduce calories by 123.36 cal/gr, each increase of 1 % ar the value of ash content will reduce coal calorific value by 78.76 cal/gr. The change in value is due to the occurrence of contamination in the stockpile area, the occurrence of swabakar in the stockpile, and the influence of high rainfall on coal